Volume 1: Codes and Standards 2012
DOI: 10.1115/pvp2012-78340
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Crack Initiation of 304L Stainless Steel in Simulated PWR Primary Environment: Relative Effect of Strain Rate

Abstract: The French Regulatory Commission insisted on a survey justifying the assumed mechanical behavior of components exposed to Pressurized Water Reactor (PWR) water under cyclic loading without taking into account its effect. In the US and Japan, the fatigue life correlation factors, so called Fen, are formulated and standardized on the basis of laboratory data to take into account the effect on fatigue life evaluation. However, the current fatigue codification, suffers from a lack of understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…5 F en value for stainless steels prescribed in the JSME code depends on the strain rate and temperature. [6][7][8][9] The same F en value is applied regardless of the applied strain range when the strain ranges are more than 0.22%, which corresponds to the fatigue limit. When the strain ranges are 0.22% or less, the environmental effect is not considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 F en value for stainless steels prescribed in the JSME code depends on the strain rate and temperature. [6][7][8][9] The same F en value is applied regardless of the applied strain range when the strain ranges are more than 0.22%, which corresponds to the fatigue limit. When the strain ranges are 0.22% or less, the environmental effect is not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Through extensive test campaigns, the value of F en has been determined empirically and summarized in assessment guidelines, such as the fatigue assessment guideline issued by the Japan Society of Mechanical Engineers (JSME) (hereafter, called JSME code) and the Boiler and Pressure Vessel Code of the American Society of Mechanical Engineers . F en value for stainless steels prescribed in the JSME code depends on the strain rate and temperature . The same F en value is applied regardless of the applied strain range when the strain ranges are more than 0.22%, which corresponds to the fatigue limit.…”
Section: Introductionmentioning
confidence: 99%
“…The JSME code gives F en of stainless steel for the water environment of a pressurized water reactor (PWR) as ln()Fen={}3.910ln()italicdεitalicdt×()0.000782T, where dε / dt (unit: %/s) and T (unit: °C) denote the strain rate and temperature, respectively. Test results revealed that the degree of fatigue life reduction of stainless steels was dependent on the strain rate and temperature 8–11 . Figure 1 shows F en for T = 598 K (325°C).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 13 pointed out that the hydrogen enhanced localized plasticity (HELP) mechanism caused more damage particularly at low strain rate. Huin et al 11 suggested that the early initiation as well as propagation of micro‐cracks were relevant parameters to explain how the strain rate affects the stainless steel fatigue life in the PWR water environment. However, as far as present author's knowledge, no theoretical or mechanistic explanation has been given for F en having the upper limit at dε / dt = 0.0004%/s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation